2012
DOI: 10.2149/tmh.2012-10
|View full text |Cite
|
Sign up to set email alerts
|

A Surveillance Model for Human Avian Influenza with a Comprehensive Surveillance System for Local-Priority Communicable Diseases in South Sulawesi, Indonesia

Abstract: The government of Indonesia and the Japan International Cooperation Agency launched a three-year project (2008–2011) to strengthen the surveillance of human avian influenza cases through a comprehensive surveillance system of local-priority communicable diseases in South Sulawesi Province. Based on findings from preliminary and baseline surveys, the project developed a technical protocol for surveillance and response activities in local settings, consistent with national guidelines. District surveillance offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Slowness of non-electronic reporting system would make it difficult to analyze the information ( Nnebue, Onwasigwe, Ibeh, & Adogu, 2013 ). Development of electronic systems can be used as quick, efficient, effective and affordable tools for this purpose ( Hanafusa et al, 2012 ; Turner, Reeder, & Ramey, 2013 ). In this study, the expert believed that, one of the weaknesses of the hospital surveillance system is the unavailability of a comprehensive electronic network in health system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slowness of non-electronic reporting system would make it difficult to analyze the information ( Nnebue, Onwasigwe, Ibeh, & Adogu, 2013 ). Development of electronic systems can be used as quick, efficient, effective and affordable tools for this purpose ( Hanafusa et al, 2012 ; Turner, Reeder, & Ramey, 2013 ). In this study, the expert believed that, one of the weaknesses of the hospital surveillance system is the unavailability of a comprehensive electronic network in health system.…”
Section: Discussionmentioning
confidence: 99%
“…Develop clear job duties for clinical staff of hospitals and the person who is responsible for communicable disease reporting, as well as training courses in cooperation with the various sectors of health system can be effective to eliminate these obstacles and problems ( Perry et al, 2007 ; Yoo et al, 2009 ; Tan, Chang, Tseng, & Lin, 2007 ; Hanafusa et al, 2012 ; Dixon, Grannis, & Revere, 2013 ; Karami & Abedini, 2012 ). In Iran, even though, there is a general guideline for surveillance and reporting of communicable diseases, but in the case of hospitals, which have unique properties, it isn’t considered distinct guideline and followed the same general guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveillance data generated through these systems are used for making policy decisions, identifying priority issues, planning and implementing surveillance programmes and allocating funds and resource in relation to communicable disease prevention and control (Calain, 2007). Further, in the present context it is much used in prediction and early detection of outbreaks (Hanafusa et al, 2012;Tambo et al, 2014). Several evaluation studies on existing communicable disease surveillance systems have been reported (Green and Kaufman, 2002;Jajosky and Groseclose, 2004;Janati et al, 2015;Thacker et al, 1983).…”
Section: Introductionmentioning
confidence: 95%
“…Among these, surveillance systems for infectious diseases are critical in protecting the people from diseases, by providing necessary surveillance data for timely action (Jelastopulu et al, 2010;Kebede et al, 2011;Perry et al, 2007). Besides, newly emerging and reemerging infectious diseases and its consequences also reveal the significance of such systems (Calain, 2007;Hanafusa et al, 2012;Tambo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%